Method for accelerating biological orthogonal catalysis of acid / reduction sensitive polymer vesicles in tumor in situ
By co-delivering precursors and Cu2+ by using disulfide bond-linked hyaluronic acid-polycaprolactone copolymers, the first chelation and later catalytic behavior of programmed release control is achieved in tumor cells, solving the inefficiency and toxic side effects of the Cu catalytic system in the prior art, achieving efficient bioorthogonal catalytic treatment and improving the biosafety of the treatment.
Patent Information
- Application Number
- CN202411793402.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The prior art is difficult to safely deliver the philtrum/hydrophobic precursor and Cu2+ in tumor cells, and form a stable Cu+ structure under a complex physiological environment, resulting in inefficiency and toxic side effects of the copper catalytic system.
By using polymer vesicles formed by disulfide bond-linked hyaluronic acid-polycaprolactone copolymer, azide, alkyne and Cu2+ are separated in the internal aqueous phase, hydrophobic layer and hydrophilic surface, the first chelation and later catalytic behavior of programmed release control is achieved, and the bioorthogonal reaction efficiency of Cu+ catalyzed is improved.
It realizes efficient bioorthogonal catalytic treatment in situ of tumors, reduces the demand for exogenous copper ions, improves the biosafety of treatment, and significantly improves the efficiency of CuAAC response.
Smart Images

Figure CN119792542A_ABST
Abstract
Description
Technical Field
[0001] The technology of the present invention relates to polymer encapsulation of polymer materials, co-delivery of hydrophilic / hydrophobic precursors and copper ions, and bioorthogonal catalysis accelerated by controllable copper chelation. Background Art
[0002] The activation of traditional prodrugs depends on the body's microenvironment of acids, enzymes, thiols, reactive oxygen species, etc., and these environments are often affected by factors such as enzyme activity, age-related physiological changes, and drug interactions. Bioorthogonal catalytic therapy is an emerging prodrug treatment technology. This therapy relies solely on the efficient catalysis of transition metals, with more stable activation ability, higher tumor specificity, and lower off-target risk. Copper-catalyzed azide-alkyne cycloaddition (CuAAC) reactions frequently appear in various bioorthogonal catalytic treatment regimens, thanks to the low price and high catalytic efficiency of copper ions, simple precursor structure, good drugability of products, and stable chemical structure and in vivo metabolism. Previous studies have shown that nanomaterials can co-deliver precursors and precisely control the catalytically active monovalent copper ions (Cu + ) is beneficial to improve the efficiency of bioorthogonal catalysis. However, the limitation of copper catalytic system is copper toxicity (mainly Cu + production) and the instability of copper ions (e.g., divalent copper (Cu 2+ ) will be reduced by alkynes; Cu + The bottleneck of existing nanotechnology is that it cannot safely deliver hydrophilic / hydrophobic precursors and Cu together. 2+ , and the formation of stable Cu in the complex physiological environment of tumor cells + The technical bottleneck leads to inefficient in vivo delivery and in situ catalysis, followed by the toxic side effects of high-dose copper ions.
[0003] The problems faced by copper-catalyzed bioorthogonal reactions are: 2+ Will be reduced by alkynes to Cu + ;Cu + Prone to oxidation or disproportionation; the reaction requires a stable Cu + structure; systemic toxicity of copper ions. These bottlenecks mean that there is still room for improvement in bioorthogonal catalytic therapy, which can further improve the in situ catalytic efficiency of tumors, reduce the dose of exogenous copper ions, and improve biosafety. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to propose a method for accelerating bioorthogonal catalysis in situ in tumors using acid / reduction-sensitive polymer vesicles. The polymer vesicles formed by disulfide-linked hyaluronic acid-polycaprolactone copolymer (HA-SS-PCL) can spatially bind azide, alkyne and Cu 2+Separated in the inner aqueous phase, hydrophobic layer and hydrophilic surface, an efficient precursor / catalyst co-delivery system is realized. By adjusting the molecular weight of the hydrophilic and hydrophobic segments of the copolymer, nanovesicles with stable structure under normal physiological environment and rapid response under acid / reduction environment are prepared. In the tumor cell environment, the surface membrane of the vesicle is perforated, so that the hydrophilic precursor (azide) in the inner aqueous phase is preferentially released from the inside out and interacts with the Cu near the surface layer. + Chelation; Subsequently, the nanovesicles further disintegrate in an acid / reducing environment, slowly releasing the hydrophobic precursor (alkyne). The formation of the chelate helps stabilize the Cu + The structure of the azide group and Cu + distance of the catalytic center, thereby increasing the Cu + The efficiency of the catalytic bioorthogonal reaction. This chelation-first, catalysis-later behavior controlled by the programmed release of nanovesicles achieves efficient bioorthogonal catalytic therapy in situ in the tumor, making the nanotherapy require less copper ions and reducing the biosafety risk caused by exogenous copper.
[0005] Technical solution: The nanovesicle material formed by the acid / reduction sensitive linear copolymer of the present invention is obtained by coupling two blocks of hyaluronic acid and polycaprolactone with a specific molecular weight through a disulfide bond; the nanovesicle formed by the self-assembly of the copolymer can integrate the hydrophilic precursor Azide, the hydrophobic precursor Alkyne and the divalent copper ion Cu 2+ Physically separated in the inner aqueous phase, the hydrophobic layer and the outer surface of the nanovesicle; the nanovesicle responds to the tumor microenvironment conditions and releases the two precursors and copper ions loaded in a programmed manner. The copolymer is obtained by linearly copolymerizing hyaluronic acid and polycaprolactone of a specific molecular weight through disulfide bonds, and the high stability of the nanovesicles assembled thereby is due to the tight entanglement between the polycaprolactones in the hydrophobic layer. Under the stimulation of acid / reducing conditions, the polycaprolactone gradually undergoes hydrolysis and disulfide bond cleavage, resulting in membrane perforation, thereby triggering the hydrophilic precursors in the inner aqueous phase to be preferentially released from the inside to the outside; the hydrophobic precursors in the hydrophobic layer are slowly released as the nanovesicles continue to disintegrate.
[0006] The precursors encapsulated by the nanovesicle material include a hydrophilic precursor and a hydrophobic precursor; the hydrophobic precursor is an alkyne; the hydrophilic precursor is an azide, and also includes a precursor with increased Cu + Stability and promotion of Cu + The structure of the chelated cuprous ion with catalytic performance includes hydroxamic acid, imidazole, pyridine, quinoline, phthalocyanine, and porphyrin. In an acid / reducing environment, the hydrophilic precursor is preferentially released from the inner water phase of the nanovesicle and reacts with the Cu ions reduced by glutathione (GSH) near the surface. 2+ Chelation. The chelate can stabilize Cu +The structure of the catalyst and the shortening of the distance between the azide group and the copper catalytic center increased the rate of subsequent bioorthogonal catalysis.
[0007] The nano-vesicle material, the in vivo blood circulation time (T 1 / 2 ) for more than 8 hours, forming Cu(I)-Azide chelate in situ in the tumor, promoting bioorthogonal catalytic drug synthesis.
[0008] After intravenous injection into living bodies (BALB / c mice), the nanomaterial can significantly prolong the half-life of hydrophilic / hydrophobic precursors and utilize the tumor-targeting ability of hyaluronic acid to efficiently co-deliver precursors and copper ions to the tumor site; the special acid / reduction-sensitive structure of the nanovesicle can preferentially release the hydrophilic precursor and Cu ions through membrane pore formation in the tumor cell environment. + Chelation, in situ initiated chelation-promoted bioorthogonal catalysis for therapeutics.
[0009] The preparation method of the nanovesicle material comprises the following steps: the amphiphilic copolymer hyaluronic acid-disulfide bond-polycaprolactone and the hydrophobic precursor are dissolved in a dimethyl sulfoxide solvent, the hydrophilic precursor is dissolved in an aqueous solvent, the two precursors are encapsulated in a nanovesicle composed of hyaluronic acid-disulfide bond-polycaprolactone by a solvent conversion method; and the copper ions are coordinated with the chemical groups on the hyaluronic acid on the surface of the vesicle through non-covalent forces.
[0010] In the preparation method, the molecular weight range of the copolymer hyaluronic acid-disulfide bond-polycaprolactone is 10-100 kDa, wherein the molecular weight distribution range of hyaluronic acid and polycaprolactone is 5-50 kDa.
[0011] The specific operation of the solvent conversion method of the preparation method is: under room temperature conditions, the stirring condition is 600-1200rpm, and the water solvent is added dropwise into the dimethyl sulfoxide solvent.
[0012] The preparation method comprises encapsulating the nanovesicles of the two precursors, transferring the nanovesicles to a dialysis bag, and dialysis the nanovesicles in a CuCl 2 Dialyze in aqueous solution for 1-24 hours.
[0013] The preparation method, CuCl 2 The concentration range of the aqueous solution is 0.1-10 mg / mL.
[0014] The nano vesicle material is used in preparing drugs in the field of bioorthogonal catalytic therapy.
[0015] The application of the nano vesicle material in preparing drugs for treating malignant tumors.
[0016] In the application, the malignant tumor includes breast cancer.
[0017] The nanocapsule material physically separates the precursor and the catalyst in space, which can avoid the 2+ Reduced to Cu by alkyne precursors + This produces diacetylenic byproducts and uncontrollable CuAAC reactions.
[0018] The two precursors in the nanovesicle material are two parts of the original drug. After they complete the CuAAC reaction, they have comparable drug activity compared to the original drug.
[0019] The nanocapsule material has the ability to release drugs from the inside out after membrane pore formation, that is, the pH / GSH environment in tumor cells can perforate the membrane surface of the nanomaterial, so that the hydrophilic precursor in the nanomaterial is preferentially released.
[0020] The hydrophilic precursor preferentially released by the nanovesicle material can react with the Cu ions reduced by GSH in the surface area of the nanomaterial. + Chelation to stabilize Cu + The structure and proximity of the azide group to Cu + distance, thereby improving the efficiency of copper catalysis.
[0021] The Cu + Chelated only by the precursor, without the involvement of additional ligands.
[0022] The schematic diagram of the vesicle-shaped nanoreactor formed by polymer self-assembly of the present invention initiating chelation-promoted bioorthogonal catalysis in tumor cells is shown in Figure 1 .
[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: The multi-component isolated co-delivery system based on polymer vesicles disclosed in the present invention has the following effects: (1) The hydrophilic / hydrophobic precursors and Cu are separated by the vesicle-like nanostructure. 2+ Physical separation in the inner aqueous phase, hydrophobic layer and hydrophilic surface can effectively avoid side reactions and premature reactions between the precursor and divalent copper; (2) pH / GSH-driven membrane pore behavior allows the hydrophilic precursor in the nanovesicles to be released preferentially, and the external Cu + Chelation occurs, stabilizing Cu + The structure of the azide group and Cu + distance, thereby improving the efficiency of copper catalysis; (3) three substances (Azide, Alkyne and Cu 2+ The co-delivery of ) and the enhanced catalytic efficiency after precursor-copper chelation significantly reduced the demand for exogenous copper for this therapy and improved the biosafety of the nanovesicles. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1Schematic diagram of polymersome-based nanoreactors initiating chelation-promoted bioorthogonal catalysis in tumor cells;
[0025] Figure 2 To characterize the physicochemical properties of nanovesicle PCHP under different pH, GSH or buffer environments;
[0026] Figure 3 pH / GSH-driven PCHP1 membrane perforation and programmed inside-out precursor / copper release;
[0027] Figure 4 The CuAAC reaction is accelerated by hydroxamic acid and the uncontrolled CuAAC reaction is initiated by alkynyl.
[0028] Figure 5 To characterize in vitro cellular uptake, GSH response, and antitumor effects;
[0029] Figure 6 For in vivo pharmacokinetics, drug distribution and anti-tumor experiments. DETAILED DESCRIPTION
[0030] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0031] Step 1: Synthesis of hyaluronic acid-thiopyridine (HA-SS-Py), taking 10 kDa hyaluronic acid as an example: Under nitrogen protection, HA (10 kDa, 1.000 g, 0.10 mmol) and cysteamine (0.812 g, 10.00 mmol) were dissolved in 80 mL of deionized water containing sodium cyanoborohydride (0.772 g, 10.00 mmol), and then reacted at 50 ° C and 500 rpm for 5 days. After the reaction, the mixture (HA 10000 -SH and HA 10000 -SS-HA 10000 ) was purified three times with an ultrafiltration tube (MWCO = 1000Da) and then freeze-dried (yield: 81%). Under nitrogen protection, the mixture was dissolved in a 20mM dithiothreitol (DTT) aqueous solution and then stirred for 2 days at 25°C and 400rpm. After the reaction was completed, ultrafiltration (MWCO = 1000Da) was performed three times at 4°C and then freeze-dried to obtain HA. 10000 -SH (yield 61%). 10000-SH (0.600 g, 0.06 mmol) and 2,2′-disulfide dipyridine (0.027 g, 0.12 mmol) were added to 50 mL of deionized water. The solution pH was adjusted to 2.0 with 1.0 M HCl and stirred at 25°C and 500 rpm for 24 h. After the reaction was completed, the pH was adjusted to 7.0 with 1.0 M NaOH solution and then filtered using a 0.22 μm MCE filter membrane. The product HA 10000 -SS-Py was purified by ultrafiltration (MWCO=1000Da) three times and then lyophilized to obtain (yield: 73%).
[0032] Step 2: Synthesis of hyaluronic acid-disulfide bond-polycaprolactone (HA-SS-PCL): Under nitrogen atmosphere, HA 10000 -SS-Py (0.440 g, 0.04 mmol) and PCL 6522 -SH (0.257 g, 0.04 mmol) was dissolved in 8 mL of deionized water (containing a catalytic amount of glacial acetic acid) and 15 mL of DMF solvent, and then the deionized water solution was dripped into the DMF solvent under anaerobic conditions at 25 °C and 500 rpm for 24 h. After the reaction, the product (HA 10000 -SS-PCL 6522 ) was precipitated with ice ethanol, washed with deionized water and acetone, and dried overnight in vacuum at 42°C (yield 47%). Referring to steps 1 and 2, HA 4000 -SS-PCL 5422 Made from hyaluronic acid with a molecular weight of 4000Da.
[0033] Step 3: Synthesis of the precursor 6-azidohexyl isohydroxamic acid (Azide): Hydroxylamine hydrochloride (1.623 g, 23.36 mmol) and sodium hydroxide (1.445 g, 35.04 mmol) were added to 20 mL of methanol and reacted at 25°C for 30 minutes. Then, methyl 6-azidohexanoate (0.530 g, 2.94 mmol) was dropped into 10 mL of the above methanol solution and reacted at 25°C and 500 rpm for 30 minutes. After the reaction was completed, methanol was removed by rotary evaporation and then dissolved in 20 mL of deionized water. After the pH was adjusted to 6.0, it was quickly extracted with ethyl acetate and then rotary evaporated. The yield was 88%.
[0034] Step 4: Preparation of polymer vesicles co-loaded with precursor and copper: 10000 -SS-PCL 6522 For example: 20 mg of HA 10000 -SS-PCL 6522and 5.0 mg of 2-ethynylquinoline (Alkyne) were dissolved in 5 mL of dimethyl sulfoxide (DMSO). Then, 5 mL of deionized water containing 5.0 mg of Azide was dripped into the DMSO phase and vigorously stirred at 800 rpm for 20 minutes. The mixed solvent was then transferred to a dialysis bag (MWCO 8-14 kDa) and dialyzed in deionized water for 24 hours, after which the polymer vesicles (PHP1) loaded with the precursors (Azide and Alkyne) were collected. The dialysis bag containing PHP1 was immersed in a 1 mg / mL CuCl2 solution and dialyzed for 3 hours to obtain PCHP1, which was then dialyzed with deionized water for 48 hours to remove excess CuCl2. See the schematic diagram of the preparation process. Figure 2 A.
[0035] PHP2 and PCHP2 were prepared by following the above steps, except that HA 10000 -SS-PCL 6522 Change to HA 4000 -SS-PCL 6522 Prepared.
[0036] Physicochemical properties of PCHP1 and PCHP2. The physicochemical characterization of PCHP1 and PCHP2 was performed, including particle size, polydispersity index (PDI), zeta potential, storage and circulation stability, and pH / GSH response of the aggregates. The aggregates were dispersed in 0.01 M phosphate buffer (PB) under different conditions (pH 7.4, pH 6.5, pH 5.0, and pH 5.0 / GSH) and 10% fetal bovine serum (FBS). Particle size and PDI ( Figure 2 B, 2C), zeta potential ( Figure 2 D) The morphology, type and distribution of micro-region elements were observed using transmission electron microscopy. Figure 2 E shows that the particle size of PCHP1 in PBS and FBS changes less, showing higher storage stability. Figure 2 F and 2G show that PCHP1 can respond to GSH stimulation and has a more sensitive acid response ability. Figure 2 The TEM-EDS results of H showed that copper was loaded on the outer layer of PCHP1, achieving spatial separation of catalyst copper and precursor.
[0037] In vitro copper and precursor release from PCHP1. Drug release from PCHP1 was determined by dialysis. Briefly, 1 mL of PCHP1 solution containing 6.54 μmol Azide, 6.00 μmol Alkyne and 0.31 μmol Cu(II) was placed in a dialysis bag (MWCO8-14 kDa) and then placed in a thermostatic shaker (37 °C, 100 rpm) with four PB conditions (5 mL, pH 7.4, pH 6.5, pH 5.0 and pH 5.0 / GSH). 5 ml of dialysate was collected and replaced with 5 ml of fresh PB at predetermined time intervals. Transmission electron microscopy (TEM) was used to track the degradation process of PCHP1, and HPLC and ICP-OES were used to detect the release of precursors and Cu(II).
[0038] like Figure 3 As shown, TEM images show that under pH 5.0, the membrane of PCHP1 is perforated; under pH 5.0+GSH conditions, the membrane pore process is accelerated, resulting in complete disaggregation of PCHP1. Drug release experiments show that the release rate of the hydrophilic precursor Azide within 6 hours is much higher than that of the surface copper ions and the hydrophobic precursor Alkyne. Therefore, the membrane pore formation of PCHP1 in the tumor cell microenvironment will cause the Azide in the inner water phase to diffuse through concentration and be preferentially released from PCHP1. Subsequently, under the accelerated driving of GSH, the disaggregated polymer vesicles gradually release copper ions and Alkyne. These data indicate that PCHP1 has the ability to release drugs in a programmed manner.
[0039] Determination of copper (I) chelate. Mass spectrometry confirmed the presence of Cu(I)-azide and Cu(I)-SAHA-D complexes. Methyl 6-azidohexanoate (without hydroxamic acid moiety) and Azide (with hydroxamic acid moiety) were added to 1 mL of a mixed solvent (CH300) containing 5 mol% Cu(II) and 10 mM GSH at equimolar concentrations (20 mM). 3 CN:PBS=1:5, v / v), stirred at 500 rpm for 1 h at 25℃, and then used as a sample for testing. In addition, Azide (6.6 mM), Alkyne (6.0 mM), Cu(II) (0.3 mM) and Glutathione (10.0 mM) were dissolved in 1 mL of mixed solvent (CH 3 CN:PBS=1:5, v / v), stirred at 25°C, 500 rpm for 1 hour, and then used as samples for testing. All samples were detected by MODI-TOF mass spectrometry.
[0040] In vitro kinetic analysis of CuAAC reactions with or without hydroxamic acid fragments. 2O:DMSO-d6=3:2, v / v), 22 mM Azide, 20 mM Alkyne, 100 mM NaAsc and 1 mM CuCl 2 The reaction was carried out in a 2 mL centrifuge tube at 37°C and 900 rpm. The concentration of each mixture was measured after a preset time period (0, 10, 30, 60, 360 min). 1 H NMR spectrum. The yield of CuAAC reaction was calculated by the ratio of the integrated areas of the characteristic peaks.
[0041] In vitro CuAAC reaction with or without glutathione. In the GSH group, PCHP1 was immersed in 0.01 M phosphate buffered saline (PBS) containing 10 mM GSH and stirred at 300 rpm at 25 °C for a predetermined time. In the group without GSH, the precursor (Azide+Alkyne), precursor / Cu(II) and PCHP1 were mixed in a solvent (CH 3 CN:PBS=1:5, v / v), stirred at 300 rpm at 25℃ for a predetermined time. The molar ratio of azide, alkyne and CuCl2 was 1.1:1:0.05. All samples were analyzed by MODI-TOF MS detection and HPLC (C18 column (25cm×0.46cm, Syncronis TM ), eluted with 60% CH3CN and 40% water, flow rate 0.8 mL / min).
[0042] like Figure 4 As shown in AC, the fragmentation peaks of the Cu(I)-Azide complex and the fragmentation peaks of the Cu(I)-SAHA-D complex can be found by mass spectrometry, which indicates that the precursor and its product can act as a chelate to stabilize the structure of copper ions. The effect of hydroxamic acid on the catalytic rate was tracked by hydrogen nuclear magnetic resonance spectroscopy. Figure 4 As shown in DF, when the reaction group contains a precursor with a hydroxamic acid fragment, a higher yield is maintained at different time periods. + The catalytic efficiency of CuAAC was increased by about two times. The data of mass spectrometry and hydrogen spectrum showed the possibility that the precursor chelated copper ions could accelerate the reaction rate of CuAAC. In addition, as shown in Figures G and H, the precursor and Cu 2+ After mixing, the product SAHA-D was generated, which was attributed to Cu 2+ The redox side reaction with Alkyne, Cu ions reduced by alkynyl groups, induces CuAAC reaction. PCHP1 spatially separates the precursor and copper ions, thus preventing the occurrence of side reactions.
[0043] Coumarin 6 / Rhodamine B@HA 10000-SS-PCL 6522 (CRHP) and GSH tracer Cu@HA 10000 -SS-PCL 6522 Preparation of CRHP (GCHP). CRHP and GCHP were prepared by solvent switching. Briefly, 20 mg HA 10000 -SS-PCL 6522 5.0 mg of coumarin 6 was dissolved in 5 mL of DMSO. Then, 5 ml of Milli Q water containing 5.0 mg of rhodamine B was added dropwise to the DMSO phase under vigorous stirring at 800 rpm, and stirring was continued for 20 minutes. The solution was transferred to a dialysis bag (MWCO 8-14 kDa) and dialyzed against deionized water for 24 hours to collect CRHP. According to the PCHP1 preparation protocol, 20 mg of HA was used 10000 -SS-PCL 6522 , 5.0 mg of GSH tracer, CuCl2 solution (1 mg / mL) were used to prepare GCHP. The contents of coumarin 6 (λexc = 450 nm, λem = 505 nm), rhodamine B (λexc = 553 nm, λem = 610 nm) and GSH tracer (λexc = 520 nm, λem = 580 nm) in CRHP and GCHP were determined by fluorescence spectrometer.
[0044] Cellular uptake of CRHP and GCHP. MCF-7, 4T1 and 293T cells were seeded in 35 mm confocal culture dishes (1×10 5 The cells were cultured in 4% paraformaldehyde (4%, v:v) for 10 min, stained with DAPI for 6 min, and then rinsed with cold PBS for 3 times. The cells were then observed by confocal laser scanning microscopy (CLSM). 293T, MCF-7, and 4T1 cells were treated with GCHP for 2 h, and the same pre-staining steps as above were performed before CLSM imaging.
[0045] Cytotoxicity test. The relative cell viability was determined by cell titer-fluorescence (CTG). MCF-7, 4T1 and 293T cells were seeded in 96-well cell culture plates (5 × 10 cells per well). 3 The cells were cultured in 4% paraformaldehyde (Azide, Alkyne, SAHA, SAHA-D, Precursors (Azide+A1kyne), Precursors+Cu(II) and PCHP1) for 24 h, then the old culture medium was removed and new culture medium containing different concentrations (0-25 μM) of drugs was added. After 48 h of co-incubation, 20 μL of CTG solution was added to each well, equilibrated at room temperature for 10 min, and the luminescence intensity was measured with an ELISA reader. The relative cell survival rate was calculated as follows:
[0046] Relative activity (%) = (Lum treat -Lum blank ) / (Lum control -Lum blank )×100%
[0047] like Figure 5 As shown, laser confocal images show that CRHP polymer vesicles loaded with hydrophobic coumarin 6 and hydrophilic rhodamine B can produce time-dependent rapid accumulation in tumor cells, thanks to HA targeting CD44 overexpressed on the tumor cell membrane. GCHP loaded with GSH tracer is not activated in normal cells, but is activated in large quantities in tumor cells, showing that polymer vesicles tend to aggregate, degrade and release drugs in a high GSH environment. Cytotoxicity experiments show that PCHP1 has a significant inhibitory effect on tumor cells, and has no obvious toxicity to normal cells.
[0048] Pharmacokinetics and biodistribution. 4T1 tumor-bearing mice were randomly divided into two groups (n=3) and intravenously injected with precursor + Cu(II) and PCHP1 (Azide=190μg, Alkyne=150μg, Cu(II)=3μg). Blood samples were collected at 0.5h, 1h, 3h, 6h, 12h, and 24h, respectively; tumors were collected at 3h, 12h, and 24h, respectively. After RIPA lysis, homogenization, acetonitrile extraction, and filtration of tumor tissues, the contents of Azide, Alkyne, and SAHA-D in each sample were analyzed by HPLC.
[0049] In vivo tumor inhibition. 4T1 tumor-bearing mice were randomly divided into 5 groups (n=6) and intravenously injected with normal saline (control group), precursor (Azide+Alkyne), SAHA-D, precursor+Cu(II) and PCHP1 (Azide=1.9mg / kg, Alkyne=1.5mg / kg, SAHA-D=3.1mg / kg, Cu(II)=30μg / kg) on days 0, 3, 6 and 9, respectively. Tumor volume and body weight were monitored during treatment. When the average tumor volume of the control group reached ~1500mm3 (day 12), the mice were killed and the tumors were recorded. Afterwards, the tumors were weighed and photographed. Figure 6 .
[0050] like Figure 6 As shown in Figure 2, pharmacokinetic and drug distribution experiments showed that the co-delivery ability of PCHP1 made the drug half-life of Azide and Alkyne similar and prolonged, and the tumor specificity of PCHP1 made the precursors enriched in the tumor site. In addition, due to the chelation promotion effect of the precursors, Cu +The catalytic reaction proceeded rapidly, and the generation rate of SAHA-D increased from 0.74 μg / h to 1.46 μg / h. The efficient co-delivery of precursors and copper ions, and the chelation-first and catalytic-later behavior controlled by the programmed release of PCHP1, achieved efficient bioorthogonal catalytic therapy in situ in the tumor, making the nanotherapy low in demand for copper ions and reducing the biosafety risks brought by exogenous copper. At this time, the catalytic efficiency after chelation promotion was normalized with the total copper ion dosage (0.1 mg / kg), and the results showed that the catalytic efficiency increased by 2800% per milligram of copper ions in one kilogram of mice. These data indicate that the excellent therapeutic effect of PCHP1 benefits from reliable precursor / copper separation and co-delivery, tumor-specific distribution, and accelerated bioorthogonal catalysis in tumor cells.
Claims
1. A nanovesicle material formed by an acid / reduction sensitive linear copolymer, characterized in that: The linear block copolymer is obtained by coupling two blocks of hyaluronic acid and polycaprolactone of specific molecular weight via disulfide bonds; The nanovesicles formed by the self-assembly of the copolymer can integrate the hydrophilic precursor Azide, the hydrophobic precursor Alkyne and the divalent copper ion Cu 2+ Physically separated into an inner aqueous phase, a hydrophobic layer and an outer surface of the nanovesicle; the nanovesicle responds to tumor microenvironment conditions and programmedly releases the two loaded precursors and copper ions.
2. The nanovesicle material according to claim 1, characterized in that The precursors encapsulated by the nanovesicle material include a hydrophobic precursor and a hydrophilic precursor; the hydrophobic precursor is an alkyne; the hydrophilic precursor is an azide, and also includes a precursor with increased Cu + Stability and promotion of Cu + The structure of chelated cuprous ions with catalytic performance includes hydroxamic acid, imidazole, pyridine, quinoline, phthalocyanine, and porphyrin.
3. The nanovesicle material according to claim 1 or 2, characterized in that: The in vivo blood circulation time (T 1 / 2 ) for more than 8 hours, forming Cu(I)-Azide chelate in situ in the tumor, promoting bioorthogonal catalytic drug synthesis.
4. A method for preparing the nanovesicle material according to claim 1, characterized in that: The following steps are involved: The amphiphilic copolymer hyaluronic acid-disulfide bond-polycaprolactone and the hydrophobic precursor are dissolved in a dimethyl sulfoxide solvent, and the hydrophilic precursor is dissolved in an aqueous solvent. The two precursors are encapsulated in polymer vesicles composed of hyaluronic acid-disulfide bond-polycaprolactone by a solvent conversion method; copper ions are coordinated with chemical groups on the hyaluronic acid on the surface of the vesicles through non-covalent forces.
5. The preparation method according to claim 4, characterized in that: The molecular weight range of the copolymer hyaluronic acid-disulfide bond-polycaprolactone is 10-100 kDa, wherein the molecular weight distribution range of hyaluronic acid and polycaprolactone is 5-50 kDa.
6. The preparation method according to claim 4, characterized in that: The specific operation of the solvent conversion method is: under room temperature conditions, the stirring condition is 600-1200 rpm, and the water solvent is added dropwise into the dimethyl sulfoxide solvent.
7. The preparation method according to claim 4, characterized in that: The polymer vesicles after encapsulating the two precursors were transferred to a dialysis bag and dialyzed in a CuCl2 aqueous solution for 1-24 hours.
8. The preparation method according to claim 7, characterized in that: The concentration range of CuCl2 aqueous solution is 0.1-10 mg / mL.
9. Use of the nanovesicle material according to claim 1 in preparing drugs in the field of bioorthogonal catalytic therapy.
10. Use of the nanovesicle material according to claim 1 in preparing drugs for treating malignant tumors.
Citation Information
Patent Citations
Double-sensitive disintegrating nano-sized vesica medicine carrier preparation and preparation method thereof
CN103251561A